Mitigation of Bullwhip Effect in Closed-Loop Supply Chain Based on Fuzzy Robust Control Approach - Zhang, Songtao; Zhang, Min (Complexity (New York, N.Y.), 2020)
Uncertainties and lead times make the closed-loop supply chain (CLSC) more complex, less stable, and then the bullwhip effect (BE) will become more intense. This paper will address a fuzzy robust control (FRC) approach to mitigate the BE in the uncertain CLSC with lead times. For the reverse channels for products in the CLSC, the customers’ used products are recycled by both the manufacturer and the third party recovery provider, and new products bought by customers within a certain period of time can be returned to the retailer. In the CLSC system, the state transformation equations of the inventories and the total operation cost are set up. A new FRC approach is proposed to mitigate the BE and realize the robust stability of the uncertain CLSC with lead times. A simulation example verifies the mitigation effect of the BE under the proposed FRC approach.